THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE LOYALTY THROUGH JOB SATISFACTION (Study on Hotel Employees in Pekanbaru) - Okta Karneli; Fitriani Fitriani (International Journal of Economics and Management Research, 2022)
This research is motivated by the importance of human resource management in moving the company. This research was conducted at the Pesonna Hotel Pekanbaru, Jalan Jendral Sudirman No. 455, Simpang Empat, Kec. Pekanbaru City, Pekanbaru City, Riau. And Batiqa Hotel Pekanbaru which is located on JL. Jend. Sudirman No. 17, Simpang Tiga, Kec. Bukit Raya, Pekanbaru City, Riau 28284, Indonesia. The purpose of this study was to determine the level of employee loyalty at Pesonna Hotel and Batiqa Hotel Pekanbaru. The sample of this study was taken as many as 79 respondents using the census method. In this study the method used is descriptive and quantitative. The data obtained from the results of the questionnaires/questionnaires were then tested using the PLS (Partial Least Square) analysis technique through the SmartPLS software. In this study the results obtained are that the work environment has a positive and significant effect on employee loyalty, the work environment has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee loyalty, and the work environment has a positive and significant effect on employee loyalty through job satisfaction at Pesonna Hotel and Batiqa Hotel Pekanbaru.